2021
DOI: 10.1155/2021/5560502
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancement in Anticancer Activity of Clinacanthus nutans (Burm. f.) Lindau

Abstract: Clinacanthus nutans is a traditional medicinal herb that is applied for the therapy of snake bites, skin infection, herpes infection, burns, scalds, dysentery, and diabetes. Clinacanthus nutans is also used to treat several cancers, including breast, cervical, colon, gastric, head and neck, liver, lung, pancreatic, and skin cancers, as well as lymphoma and leukemia; however, the underlying mechanisms of its anticancer activity remained undetermined. We searched PubMed and Google with key words “Clinacanthus nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In an experimental study conducted in 2019, CN ethyl-acetate fractions (CNEAF) were found to induce reactive oxygen species (ROS)dependent autophagy and apoptosis of HCT116 human colorectal cancer cells (11). Similar observations were made where CNEAF induced autophagy and apoptosis, increased ROS levels, dissipated mitochondrial membrane potential, increased expression of Bax, and decreased the expression of Bcl-2 and Bcl-X2 in HCT116 cell lines (12). In an in vitro investigation of the potential of CN against cancer, the chloroform extracts of CN were shown to inhibit the proliferation of 7 cancer cell lines including the human colon adenocarcinoma cell line (LS-174T) (13).…”
Section: Introductionmentioning
confidence: 63%
“…In an experimental study conducted in 2019, CN ethyl-acetate fractions (CNEAF) were found to induce reactive oxygen species (ROS)dependent autophagy and apoptosis of HCT116 human colorectal cancer cells (11). Similar observations were made where CNEAF induced autophagy and apoptosis, increased ROS levels, dissipated mitochondrial membrane potential, increased expression of Bax, and decreased the expression of Bcl-2 and Bcl-X2 in HCT116 cell lines (12). In an in vitro investigation of the potential of CN against cancer, the chloroform extracts of CN were shown to inhibit the proliferation of 7 cancer cell lines including the human colon adenocarcinoma cell line (LS-174T) (13).…”
Section: Introductionmentioning
confidence: 63%
“…39 This medicinal plant contains various phytochemical constituents, including lupeol, β-sitosterol, stigmasterol, botulin, myricyl alcohol, and a range of C-glycosyl flavones such as vitexin, isovitexin, shaftoside, isomollupentin, orientin, and isoorientin. [40][41] Pharmacologically, the leaves of Clinacanthus nutans have shown a wide range of activities, including cholinergic modulation, cytotoxicity, anti-Papillomavirus infectivity, anti-inflammatory properties, virucidal activity against varicella-zoster virus and dengue virus type 2, and antioxidant protective effects against oxidativeinduced hemolysis. [41][42] Clinically, preparations of Clinacanthus nutans, as creams, have been successfully used in treating genital herpes and varicella-zoster lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, C. nutans has been used for treating bacterial and viral infections, scalds and burns, insect and snake bites, skin rashes, gout, and diabetes [ 2 ]. Several studies have demonstrated that it has several biological activities, including anticancer, antioxidant, antidiabetic, antiviral, anti-inflammatory, immunomodulatory, and neuromodulatory activities [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%